Comparative Advantages of National Pharmaceutical Industries through the Prism of New Indicators - Salikhova, O. B. (Statistics of Ukraine, 2020)
Specific ways of the emergence of new actors in the global market of pharmaceutical goods is investigated, with substantiating the role of transnational corporations (TNC), their investment and technologies in establishing pharmaceutical industries in developing countries. The cases of Puerto Rico and Ireland are taken in order to demonstrate the background for expansion of manufacturing of medicines and medical products and analyze the tendencies in their export capacity building. The factors making pharmaceutical TNC transfer production facilities to India and China are substantiated and implications of this process are highlighted. It is revealed that due to the production internationalization, countries that had been net importers of pharmaceuticals just several decades ago have joined the group of key suppliers to external markets. Because American and European TNC are leading in the pharmaceutical industry by R&D expenditure, they are the principal holders of advanced technologies in the industry. It follows that manufacturing of medicines and medical products in most part of countries either directly or indirectly depend on innovative products of TNC and their technology transfer via various channels (both licensing and imports of components, active pharmaceutical ingredients in particular). It is shown that with the emergence of new market actors coming from developing countries, traditional approaches to determining comparative advantages of counties in the global trade need to be improved. The cases of countries that are recipients of foreign technologies, on which territories powerful high tech pharmaceutical production facilities with high shares of intermediate consumption and heavy export supplies are located due to TNC investment or local public-private capital, give evidence that the classical RCA indicator allows to measure visible comparative advantages in the trade in goods rather than revealed ones. It is proposed that analyses of advantages at country level should include the indicator of high tech goods supplies, to provide for a more accurate description of the innovation component in advanced industries. A new approach to the assessment of comparative advantages of high tech pharmaceutical manufacturing is proposed and tested, which is based on the principle of specialization and use of the ratio of Comparative Advantage in Value Added Activity (CAVA) in particular. It is revealed that the pharmaceutical industry of Ireland, Jordan, Singapore, India or Columbia, with reliance on foreign investment and technologies, could gain advantages in value added creation and dominate the national economies. It is shown that Ukraine is enhancing the advantages in value added creation in the pharmaceutical industry; is it substantiated that due to low R&D and innovation performance and heavy dependence on imported components, capacity building of this industry and its current advantages result from global tendencies and global market conjunctures rather than from the implementation of the national science & technology priorities. According to the author’s recommendation, the proposed approach to determining comparative advantages in value added creation should be used for the assessment of other high tech industries, apart from the pharmaceutical industry, and that is should be supplemented by statistical tools for analysis of foreign trade in finished and intermediate high tech goods.